Influencia de la geotécnia en la vulnerabilidad de las quebradas secas en Chosica - Canales Rivas, Diana Elizabeth (2014)
The study area covers the streams of Mariscal, Juan Carossio, La Libertad, and Corrales. These streams share the fact that its natural channel is occupied by inhabitants of the area, thus increasing the degree of vulnerability and danger of its inhabitants. Our study aims to determine the geotechnical parameters of colluvial material deposited on the slopes of the hills to be saturated by the rains from this propose solutions to minimize the impact of landslides of these mass movements of mud and stone. The methodology applied to this thesis is the review of the information related to these slides, so done field work that includes topographic, hydrologic, geologic, geotechnical information, statistics and others. Samples of material from the streams through pits was then obtained in order to perform the corresponding tests and thus determine the soil parameters that are affected by water runoff or flows by extraordinary rainfall. With the information obtained was the analysis of the results and thereby propose solutions to the problem of the 'landslides' subject of this thesis.